2019
DOI: 10.1155/2019/2152914
|View full text |Cite
|
Sign up to set email alerts
|

Control Design of the Wave Compensation System Based on the Genetic PID Algorithm

Abstract: The transfer function of the wave compensation system is deduced. The interference signal acting on the system is eliminated by the feed-forward compensation correction method. The pole assignment of the system is carried out after eliminating the interference signal. The genetic PID algorithm is proposed, and the genetic PID controller is designed. The control block diagram of the wave compensation system based on the genetic PID control algorithm is established, and the optimal index and PID parameters are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The Genetic PID control method simulates the process of natural selection and genetic mechanisms to optimize controller parameters for improved control performance. It does not require complete information about the controlled object, but it has drawbacks like high computational demands and slow convergence speed (Zhou et al, 2019;Ahmmed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Genetic PID control method simulates the process of natural selection and genetic mechanisms to optimize controller parameters for improved control performance. It does not require complete information about the controlled object, but it has drawbacks like high computational demands and slow convergence speed (Zhou et al, 2019;Ahmmed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Triet et al [7] [8] controlled the speed of the second component by adaptive fuzzy sliding mode control strategy, and the research showed that this control method had better control performance than PID control. Zhou et al [9] studied how to combine the genetic algorithm with PID in the heave compensation control. Tang [10] used a particle swarm optimization algorithm to optimize the control cofficients of the controller to improve the effect so that the system had the advantages of subtle overshoot and ripid response time.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [14] used the Lagrange kinematics equation and numerical simulation to analyze the influence of the rope length and lifting speed of the floating crane wave compensation system on the system response, which has great reference significance for the design of wave compensation systems. Zhou et al [15] proposed a genetic PID (proportionalintegral-differential) controller with feedforward compensation for compensating cranes to optimize the optimal indicators and PID parameters of the system. While maintaining system stability and accuracy, it improved the system's fast response ability and achieved good control results.…”
mentioning
confidence: 99%